Reverberation time of Wrocław Opera House after restoration - Rudno-Rudziński, Krzysztof; Dziechciński, P. (Archives of Acoustics, 2006)
One of the main acoustic goals set prior to restoration work on the Wrocław Opera House in 1997 was to increase the auditorium’s reverberation time. Now, after the completion of the restoration work, comprehensive acoustic investigations of the Opera House, including reverberation time, were carried out. Measurements were performed in accordance with the ISO 3382. The reverberation time measurement results were analysed with regard to the absorption coefficient of seats. After the seats were installed, the effect of acoustic coupling with the stage and also the position of the orchestra pit’s movable floor was investigated. The effect of the location of a sound source (on the stage and in the open and covered part of the orchestra pit) on reverberation time was examined. The differences in reverberation time between the measurement locations were compared with the differences in reverberation time between the sound source locations. The current and pre-restoration reverberation time values were compared. It was found that the acoustic goal set for the restoration of the Opera House was achieved.